Emmanuel Lévinas's criticism of Parmenides's philosophy - Kubok, Dariusz (Folia Philosophica, 2003)
The present article is an attempt at analysing E. Levinas’s attitude towards ancient philosophy as exemplified by the views of Parmenides of Elea. Levinas, while criticising the ontological tradition of Western philosophy, identifies its source in Parmenides’s philosophy, which is thus indirectly held responsible for a totalising way of thinking that negates the transcendental. Levinas sharply contrasts this tradition with the metaphysics of the Infinite, he also opposes otherness to identity, and autonomy to heteronomy. It is then worth our while to consider the sources of this criticism, and the grounds for Levinas’s objections against Western ontology.